A New IoT Combined Body Detection of People by Using Computer Vision for Security Application - Othman, Nashwan Adnan; Aydin, Ilhan (Ieee, 2017)
In recent years, the security constitutes the most important section of our lives. Automation of a home is an exciting field for security applications. This area has developed with new technologies like Internet of things (IoT). In IoT, each device behaves as a small part of an internet node and each node communicate and interact. Currently, security cameras are used in order to construct safety areas, cities, and homes. The camera records the images and, when a problem occurs, the problem is detected by monitoring the old record. In this study, an IoT-based system is combined with computer vision in order to detect the people. A Raspberry PI 3 card with the size of a credit card was used for this purpose. A motion is detected by the PIR sensor mounted on the Raspberry PI. PIR sensor helps to monitor and get alerts when movement is detected. Afterward, human is detected in the captured image and sends images to a Smartphone by using telegram application.
9th International Conference on Computational Intelligence and Communication Networks (CICN) -- SEP 16-17, 2017 -- Final Int Univ, Girne, CYPRUS
Keywords: Terms-Human detection; Internet of things; telegram; Computer Vision; Raspberry PI